Impact of Pitching on Infraspinatus Muscle Elasticity in High School Baseball Pitchers: A Continuous Shear Wave Elastography Study - Hitoshi Shitara; Ren Koda; Tsuyoshi Tajika; Tsuyoshi Sasaki; Masataka Kamiyama; Ryosuke Miyamoto; Yuhei Hatori; Koichiro Yanai; Kurumi Nakase; Fukuhisa Ino; Takuma Kachi; Yoshiki Yamakoshi; et al. (Diagnostics)
Background/Objectives: The repetitive overhead throwing of baseball stresses the posterior shoulder, including the rotator cuff and capsule, causing stiffness, tissue thickening, and dysfunction. Previous studies on collegiate baseball players have linked these changes to glenohumeral internal rotation deficits, pain, and injuries. However, these studies primarily used acoustic radiation force impulse-based shear wave elastography (SWE), which has limitations, including tissue heating and lack of portability. The acute effects of pitching on infraspinatus (ISP) muscle elasticity in high school pitchers remain unclear. Therefore, this study aimed to evaluate the acute impact of pitching on ISP muscle elasticity in high school baseball pitchers using continuous SWE (C-SWE), which is a safer and more portable method. The relationship between ISP muscle elasticity and pitching load was also examined. Methods: ISP muscle shear wave velocity (SWV), shoulder range of motion, and strength were evaluated in high school baseball pitchers. The participants were categorized into pitching and non-pitching groups based on whether they pitched with full effort on the day of their medical checkup. C-SWE was used to assess ISP muscle elasticity. Results: The pitching group had considerably higher ISP muscle SWV on the dominant side than the non-pitching group (p = 0.008). A significant positive correlation was observed between pitch and ISP muscle SWV (r = 0.467, p = 0.003). Conclusions: Repetitive pitching acutely increases ISP muscle stiffness in high school pitchers, contributing to posterior shoulder tightness. C-SWE is a safe and practical method for assessing tissue elasticity and developing injury prevention strategies.